Preventive CCL2/CCR2 Axis Blockade Suppresses Osteoclast Activity in a Mouse Model of Rheumatoid Arthritis by Reducing Homing of CCR2hi Osteoclast Progenitors to the Affected Bone - Flegar, Darja; Filipović, Maša; Šućur, Alan; Markotić, Antonio; Lukač, Nina; Šisl, Dino; Ikić Matijašević, Marina; Jajić, Zrinka; Kelava, Tomislav; Katavić, Vedran; Kovačić, Nataša; Grčević, Danka (Frontiers in Immunology, 2021)
Detailed characterization of medullary and extramedullary reservoirs of osteoclast progenitors (OCPs) is required to understand the pathophysiology of increased periarticular and systemic bone resorption in arthritis. In this study, we focused on identifying OCP population specifically induced by arthritis and the role of circulatory OCPs in inflammatory bone loss. In addition, we determined the relevant chemokine axis responsible for their migration and targeted the attraction signal to reduce bone resorption in murine collagen-induced arthritis (CIA). OCPs were expanded in periarticular as well as circulatory compartment of arthritic mice, particularly the CCR2hi subset. This subset demonstrated enhanced osteoclastogenic activity in arthritis, whereas its migratory potential was susceptible to CCR2 blockade in vitro. Intravascular compartment of the periarticular area contained increased frequency of OCPs with the ability to home to the arthritic bone, as demonstrated in vivo by intravascular staining and adoptive transfer of splenic LysMcre/Ai9 tdTomato-expressing cells. Simultaneously, CCL2 levels were increased locally and systemically in arthritic mice. Mouse cohorts were treated with small molecule inhibitor (SMI) of CCR2 alone or in combination with methotrexate (MTX). Preventive CCR2/CCL2 axis blockade in vivo reduced bone resorption and OCP frequency, whereas combining with MTX treatment also decreased disease clinical score, number of active osteoclasts and OCP differentiation potential. In conclusion, our study characterized functional properties of two distinct OCP subsets in CIA, based on their CCR2 expression levels, implying that CCR2hi circulatory-like subset is specifically induced by arthritis. Signaling through CCL2/CCR2 axis contributes to OCP homing in the inflamed joints and to their increased osteoclastogenic potential. Therefore, addition of CCL2/CCR2 blockade early in the course of arthritis is a promising approach to reduce bone pathology.